Hydrogen recovery from the purge stream of a cyclohexane production process using a mass exchange heuristic - Fischer, Carlos Daniel (2014)
In this paper, we propose a novel hydrogen recovery structure in a cyclohexane production process, arrived at by following a mass exchange heuristic developed in previous works [1,2]. In the cyclohexane production process considered, we explore the effect of process design variables and find the optimal design for a mass exchange between the purge stream and the feed of benzene to the process. We compare our results with a conventional process design lacking hydrogen recovery from the purge, and with a process design which implements a conventional membrane recovery system at the optimum setup of the decision variables. The process with recovery through mass exchange here proposed obtained a respectable 7.12% reduction of hydrogen consumption, resulting in an increase of the plant Net Annual Income of a 4.24% respect to the conventional process design without recovery. These figures are similar to the ones that result from implementing a process design with a conventional membrane recovery system. These results highlight the importance of considering a mass exchange between the process feed and purge stream as an alternative design of the recovery system.